CYBER VULNERABILITY IN LIGHT OF ONLINE LEARNING REALITY - Piscikiene, Inga; Romeikiene, Jurate; Šustickienė, Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Presently, as Covid 19 has caused most of educational processes to move online, cybersecurity and data protection is rapidly gaining importance in all educational institutions, and most of the academia became more vulnerable to cyberattacks. This article sheds some light on how communities of higher education institutions perceive increased online threats, what measures they take to protect themselves against cybercrime, whether they practice good security hygiene. This paper presents and analyses results of a survey conducted at higher education institutions (universities, colleges) into perception of cybersecurity, online culture and hygiene during the present times of remote education.